Examples of Signet Rings from the Vodoča Necropolis near Strumica (Archaeologia Adriatica, 2010)
Over a thousand graves were discovered at the necropolis in Vodoča near Strumica (about 170 km south-east of Skopje). Population of the settlement of Vodica – Vodoča was buried at this site over a long chronological range from the 13th/14th centuries continuously until the 20th century. Jewelry is dominant archaeological material at the Vodoča necropolis, as it is on other Christian cemeteries from the mentioned period in a wider region. Several interesting examples of rings with sphragistic purpose which were studied in this paper can be broadly dated from the second half of the 14th century to 17th century. Besides complete or reduced signs, and heraldic or emblematic ones, over the course of time one can also notice reduction in quality and poor characteristics of workmanship and material. Tendency to preserve traditional traits is noticeable on one hand, and on the other hand there is evident penetration of oriental sphragistics. These signet rings were worn foremost by "baštinari" (heirs) mentioned in Turkish registers. They were the remains of medieval lesser nobility – "pronijari" (pronoiars) and their offspring who inherited property and land. These rings were used to legitimize investitures and membership in a certain social class and profession.
Keywords: necropolis; Vodoča; rings; sphragistics; heraldics; emblematics; "baštinari" (heirs)